Hydrogen bonds to Au atoms in coordinated gold clusters - Md. Abu Bakar (Nature Portfolio, 2017)
Many transition metals can form hydrogen bonds to organic species, but experimental evidence for Au is still lacking. Here, the authors obtain crystallographic and NMR spectroscopic evidence of hydrogen bonding between C-H groups and Au atoms of gold clusters, suggesting that non-covalent interactions may play a role in gold cluster catalysis.